Towards a framework for quantifying the population-level consequences of anthropogenic pressures on the environment: The case of seabirds and windfarms. (1st April 2017) - Cook, Aonghais S.C.P.; Robinson, Robert A.
Highlights: Quantifying impacts of development on populations is a key problem for ecologists. However, approaches to do this are often subject to significant uncertainty. We propose a framework to assess the impacts of wind farms on seabird populations. Probabilistic approaches proved less robust to uncertainty than others. Decisions about impacts must be made in the context of the population concerned.